UJI STARTER BEBERAPA ISOLAT JAMUR ENDOFIT TANAMAN CABAI MERAH TERHADAP PENYAKIT VIRUS KOMPLEKS, PERTUMBUHAN DAN HASIL TANAMAN CABAI MERAH (Capsicum annuum L.) - Arif, Haswandi; Ali, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
On of importantdiseasesfound in red chilli plants is complex virusdiseasecaused by infection of some viruses. Complex virus diseasecan decreaseyield of red chilli plants so as a control method should be aplplied up to 82.3%. The use of antagonistic fungi to induce plant resistance is one of alternative tocontrol methods of especially ageints complex virus diseases in chili plants. The objective of research is to study the effect of aplication of some starter endophytic fungi isolates from red chilli plants and obtained the best isolates to control complex virus disease and to increase red chili plants growth and yield. This reseach has been conducted experimentally by using a complete random design consisting of 5 treatment (100 g starter of endophytic fungi/plants it, e : no starter, Rhizoctonia sp.,Streptomyces sp., unidentification isolat and Chepalosporium sp.) and 4 replications. The data were analyzed statistically using analysis of variance and the mean of each treatment was compared by using Tukey’s test at the level of 5%. The results showed that the aplication endophytic fungi isolates starter from red chilli plant on soil gave no significant effect in controling complex virus disease and had not increase a red chilli plants growth and yield. Keywords :Red chilli, complex virus,endophytic fungi, resistance induction